Sex/Gender and Self-Determination : Policy Developments in Law, Health and Pedagogical Contexts - Davy, Zowie (Book collections on Project MUSE., 2021)
This book presents a poignant account of the current policy approaches to self-determining sex and gender in the UK and beyond, showing how legal, medical and pedagogical policy developments are interconnected, and how policy is affected by transgender and diverse gender experiences and activism.